REVIEW OF LEGAL PROFESSIONAL ETHICS TOWARDS INVESTIGATORS IN THE CRIMINAL CASE OF FOUR STUDENTS REFUSING OMNIBUS LAW - Dea Iswandi; Fadillah Rizky Nur Ikhlas; Ilham Khoirudin Sanjaya; M. Hanif Muflih (UNTAG Law Review, 2021)
The way investigators handled students who were involved in thedemonstration to ratify the Job Creation Act did not reflect the slogan of "protecting, nurturing, and serving the community" carried by the institution. Instead of fostering and protecting the future of students, the police criminalize them. The police arrested students and students who opposed the job creation law in a number of areas last week. The police accused them of being anarchist. The police also threatened to include the status of law violators so that they would not issue a police recordcertificate (SKCK). Student involvement in demonstrations is not a criminal act. Moreover, students' and students' criticism of the Job Creation Act is actually a reaction to the inherent defects of the omnibus law. Not only is its preparation not transparent, the substance of the universal sweeping law also harms workers and threatens the environment. The case of students who are victims of criminalization forrefusing the Omnibus Law is still continuing its legal process to this day. However, the trial which is supposed to be the place to seek justice is run very subjectively and full of flaws. This further confirms that no violation of Professional Ethics conducted by investigators to the students repellent Omnibus.